Ordinance No. 76: An Ordinance Prohibiting Deadly Weapons, July 1, 1887, reprinted in Stockton Review and Rooks County Record 1, July 1, 1887 - (:unkn) unknown (My University, 1887)
Prohibited carry of any deadly or dangerous weapons. Also prohibited carry into any church, place of public worship, school, educational center, electional location, court, or public assemblage. Includes having on or about his person any kind of fire arms, bowie knife, dirk, dagger, sling shot, or other deadly weapon. Includes prohibition of brandishing in a rude, angry, or threatening manner. Punished by a fine of ten to fifty dollars.
Keywords: BRANDISHING; CARRY; CARRY - CERTAIN PUBLIC PLACES